2013
DOI: 10.1097/tp.0b013e3182954618
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence Does Not Abrogate Engraftment of Murine Allogeneic Bone Marrow

Abstract: Advanced age does not impair bone marrow engraftment, thereby widening the clinical potential of experimental protocols inducing transplantation tolerance through mixed chimerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Recently it was reported that, despite increased memory T cell frequencies, tolerance can be established in aged mice by costimulation blockade or host T cell depletion, in conjunction with low-dose irradiation (25). We now demonstrate that radiation-free, low-intensity conditioning with Bu facilitates the generation of allogeneic tolerance via BMT-induced mixed chimerism in aged mice.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Recently it was reported that, despite increased memory T cell frequencies, tolerance can be established in aged mice by costimulation blockade or host T cell depletion, in conjunction with low-dose irradiation (25). We now demonstrate that radiation-free, low-intensity conditioning with Bu facilitates the generation of allogeneic tolerance via BMT-induced mixed chimerism in aged mice.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, tolerance cannot be achieved in mice 1 year and older via conditioning with CD45RB mAbs without thymic regeneration (24) or TBI (25). Our challenge, ultimately, was to induce allogeneic tolerance in aged mice using a radiation-free conditioning regime that caused minimal damage to the involuted thymus and did not require additional thymic enhancement.…”
Section: Allogeneic Tolerance Via Mixed Chimerism Is Achievable In Agmentioning
confidence: 99%
“…However, not all studies have found that aged mice resist transplant tolerance of skin and cardiac allografts. In one study, mice 12 months of age were susceptible to transplantation tolerance after bone marrow transplantation and treatment with costimulatory blockade (91). Differences between this study and the one described above (88) may be due to tolerance regimen and differences between studies in the ages of the mice used (88,91).…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 66%
“…In one study, mice 12 months of age were susceptible to transplantation tolerance after bone marrow transplantation and treatment with costimulatory blockade (91). Differences between this study and the one described above (88) may be due to tolerance regimen and differences between studies in the ages of the mice used (88,91). Commonly used immune suppressant medications for organ transplantation, like calcineurin inhibitors, have age-specific effects.…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 67%
“…We therefore tested BMT protocols in 12-month-old murine (aged) recipients harboring higher frequencies of Tmem cells and compared the outcome with that of 2-month-old murine recipients (young). Unexpectedly, age did not inhibit chimerism and tolerance induction through costimulation-based or T-cell depletionbased BMT protocols [34]. T-cell responses (i.e., proliferation and IFN-γ production) were found to be significantly increased in old (naïve) mice over young mice upon polyclonal stimulation, but…”
mentioning
confidence: 84%